Hubungan Antara Minat Belajar dengan Penguasaan Konsep Siswa Kelas XI MIA pada Pembelajaran Biologi - Edi Kurniawan; Gufron Amirullah; Luthpi Safahi (IAIN Ternate, 2021)
This study aims to determine the level of the relationship between students' learning interest with concepts mastery. This research was conducted at SMAN 7 Bekasi in East Jakarta. The population of this study is 35 students at eleventh grade of SMAN 7 MIA in East Jakarta Bekasi academic year 2014/2015. The sampling technique was cluster random sampling. The sample in this research is eleventh grade of MIA 2. This study uses a quantitative correlation approach associative. Data analysis technique used is linear regression. Both variables do not have a linear relationship (F_hit = 1.25 < F0, 99 (16/17) = 3.27) with the regression equation is y = 81.57 + -0,46x. Its mean that every one time improving learning will increase the ability of mastering the concept of 0.54. The calculation results obtained r_hit correlation coefficient = -0.26 < r0,95 (33) = 0.334 which means that Ho is accepted. It was concluded that there was no relationship between the students’ learning interest with the concept mastery.